Algebra Practice 2

Algebra Practice 2 - x = e 2 x 2e x 3 = 0 1 x = 1 x 8 x 3 =...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: x = __________ e 2 x - 2e x - 3 = 0 1 x = __________ 1 x - 8 x 3 = 0 2 x = __________ 2 x = 3e 4 x x = __________ 1 - 1 = k 1+ x x = __________ e x - 2 = k 4 x x = __________ 4 x 3e kx - 16 xe kx = 0 x = __________ 2 ln(5 x) = ln( x + 2) x = __________ ( 2 x + 5) 2 + 5( 2 x + 5) - 36 = 0 x = __________ 102 x + 3 10 x - 10 = 0 x = __________ 3 2 2t - 11 2t - 4 = 0 x = __________ x + 9 - 2 = x - 3 ( ) ( ) ( ) x = __________ x - 2 = 1 12 x x x = __________ 1 + 1 - 6 = 0 x +8 x +8 x = __________ x 4 + 2 x 2 = 3 x = __________ 1 + 4 = 1 x -1 5 x = __________ ( x + 5)( x - 2) = 8 z = __________ 3az + 1 = 3a - 4 z z = __________ 12 - 7 = 1 z z +1 y = _________ 0 = 12 y 2 + 12 y - 24 w = _________ ln(w + 2) = ln( w) + ln ( 5) t = __________ P = 10e kt t = __________ 2t = et - 2 t = __________ t 2 e 3t + 9te 3t = 0 t = __________ ln( t ) + ( 2t ) = ln( 8) t = __________ 5 log(t ) = 3 t = __________ t 4 - 9t = 0 2 n = ________ n - 2 ( 3n + 5) = 0 n-3 2 2 p = _________ p - 5 ( p + 3) = 0 p +1 w = ________ log(w) + log(w + 1) = log(20) 2 ( ) ( ) L = _________ T = 1 2 L g = __________ (1 - 2 )( + ) - ( - 2 ) = 0 k x 2 + r02 x = __________ D = _________ x = __________ x = __________ w = _________ Simplify 2x 2 3 =0 2 x 2 + r 2 32 0 1 1 - 2 - - =0 2 2 2 2 2 D a D 1+ 1+ D D -3 -3 - 14kx + 2k ( 20 - x ) = 0 Assume k 0 25 x - 20 = 0 1200 2 + x 2 Assume V > 0 - 5.12Vw -2 + 10 w = 0 ( ( + ) ) - kx 3 ( x 2 2 2 3 2 Assume > 0 2 + r02 ) ( 2x) 1 2 ( ) hint: Do not expand the power (x 2 - 3 2x - 2 ) (x -3 ) 2 2 -13 2 x x -3 3 = 3 2 ( ) 1- 1 -x x 1 x ...
View Full Document

This note was uploaded on 04/02/2008 for the course MATH 124 taught by Professor Kennedy during the Spring '08 term at Arizona.

Ask a homework question - tutors are online